The role of stress in heart failure – ground for sex specific pathophysiology - Heffer, M.; Zibar, L.; Viljetic, B.; Makarovic, Z. (Вiopolymers and Cell, 2011)
In the last hundred years modern society went through numerous changes in life style, dietary habits, work load, physical activity and other environmental factors. As a species we are not well adapted to new demands. Higher levels of stress hormones provoke various effects, especially gradual change in the sensitivity of adrenergic, glucocorticoid and insulin receptors. All these changes are mutually associated and they gradually lead to metabolic syndrome, obesity, diabetes, heart failure and other types of pathology depending on genetic makeup and environmental factors. The aim of this paper is to summarize current knowledge concerning the impact of stress on cardiac function. Whereas stress response is sex specific we would emphasize a potential difference in pathophysiology of ischemic heart failure in men and women. Modern medicine has misinterpreted autonomous nervous system functions for years and this was reflected in heart failure (HF) and arterial hypertension therapy. Stress before the onset of menopause has a lesser effect on cardiac function compared to stress after menopause. Postmenopausal women have a significantly higher risk of heart disease, which is related to the diminished protection of the female hormonal cycle, but low doses of estrogen have not proven protective in postmenopausal women. Potential new targets of sexspecific cardiac therapy would come from better understanding of the molecular mechanisms exerted by nuclear receptors for steroid hormones, transcription factors involved in heart remodeling, cross-talk in adrenergic signaling pathways and their down-stream molecules. Keywords: heart failure, stress, adrenergic receptors, sex specific.